(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
Medicinal plants are the source of treatment for many diseases and ailments throughout the developing world. Studies on them could lead to the finding of novel drugs for effective treatment of various diseases. We have chosen one of the most commonly used plants of Cymbopogon citrates leaves for the present study which was screened for phytochemical and antibacterial properties. The antibacterial activity test was evaluated qualitatively through the use of diffusion method on a solid medium and direct contact method using the following microbial isolate: Staphylococcus aureus, and E. coli. The study revealed that Cymbopogon citrate extracts contained rich availability of tannins, flavonoids, saponins, glycoside, alkaloids and steroids as the secondary metabolites. Furthermore, the extracts of plant leaves were found to have possessed the antibacterial properties for wide a range of gram-positive and gram-negative bacterial strains and demonstrated the best inhibition against Escherichia coli with an inhibition zone of 21 mm at a concentration 300 mg/ml.